Analytical Evaluation of Four Accessions of Dialium guineense (L.) Leaves - Lanre, Awotedu Olamilekan; Sesan, Ariwoola Oluwole; Eccepacem, Chukwudebe; Mbechun, Ajekigbe Joyce (International Journal of Sustainable Agricultural Research, 2020)
The study evaluates the diversity of accessions of Dialium guineense collected from four different eco-geographical zones of Nigeria. Physicochemical composition was undertaken using the parameters recommended by WHO. The physicochemical parameters evaluated in this study include; the ash values (Loss on drying, Water- soluble Ash, Total ash content, acid insoluble ash, Nitrated ash, Sulphated ash), the exhaustive extraction was done using various solvents: Ethyl-acetate, Methanol and Aqueous with increasing polarity using soxhlet apparatus. Proximate composition which includes; crude fibre, crude protein, crude fat and total carbohydrate were investigated and organoleptic characters and the PH of the plants across the accessions were also investigated. Physicochemical and Proximate parameter investigated shows a reasonable amount of the nutritional composition of the plants for all the accessions. Organoleptic characters evaluated include; taste, odour, colour, sand and silica, insect infestation and rodent infestation, while the PH for all the accessions ranges from 6.0-6.5. Significant differences were observed between the studied parameters across the accessions. Variations observed in the results of this physicochemical evaluation could be pioneered by several factors such as environment, habitat, age of plant, season and chemical race of plants. Thus, from the observed result, it is expected that the physicochemical and proximate properties of this genotype will be very useful in the quality of the plant and also in the nutritional composition of the plant.